Identification of Cryptosporidium Species in Fish from Lake Geneva (Lac Léman) in France. - Gabriela Certad; Jean Dupouy-Camet; Nausicaa Gantois; Ourida Hammouma-Ghelboun; Muriel Pottier; Karine Guyot; Sadia Benamrouz; Marwan Osman; Baptiste Delaire; Colette Creusy; Eric Viscogliosi; Eduardo Dei-Cas; et al. (PLoS ONE, 2015)
Cryptosporidium, a protozoan parasite that can cause severe diarrhea in a wide range of vertebrates including humans, is increasingly recognized as a parasite of a diverse range of wildlife species. However, little data are available regarding the identification of Cryptosporidium species and genotypes in wild aquatic environments, and more particularly in edible freshwater fish. To evaluate the prevalence of Cryptosporidiumspp. in fish from Lake Geneva (Lac Léman) in France, 41 entire fish and 100 fillets (cuts of fish flesh) were collected from fishery suppliers around the lake. Nested PCR using degenerate primers followed by sequence analysis was used. Five fish species were identified as potential hosts of Cryptosporidium: Salvelinus alpinus, Esox lucius, Coregonus lavaretus, Perca fluviatilis, and Rutilus rutilus. The presence of Cryptosporidium spp. was found in 15 out of 41 fish (37%), distributed as follows: 13 (87%) C. parvum, 1 (7%) C. molnari, and 1 (7%) mixed infection (C. parvum and C. molnari). C. molnari was identified in the stomach, while C. parvum was found in the stomach and intestine. C. molnari was also detected in 1 out of 100 analyzed fillets. In order to identify Cryptosporidium subtypes, sequencing of the highly polymorphic 60-kDa glycoprotein (gp60) was performed. Among the C. parvum positive samples, three gp60 subtypes were identified: IIaA15G2R1, IIaA16G2R1, and IIaA17G2R1. Histological examination confirmed the presence of potential developmental stages of C. parvum within digestive epithelial cells. These observations suggest that C. parvum is infecting fish, rather than being passively carried. Since C. parvum is a zoonotic species, fish potentially contaminated by the same subtypes found in terrestrial mammals would be an additional source of infection for humans and animals, and may also contribute to the contamination of the environment with this parasite. Moreover, the risk of human transmission is strengthened by the observation of edible fillet contamination.